The Implementation of integrated Management Information Systems in the Human Resource Management: An empirical Study of Success Factors - Nicolas Reineke (Journal of Applied Leadership and Management, 2016)
What are the determining success factors of IT implementation processes in HR environments?
Keywords: 650; IT implementation; HR environment; integrated management information system; human resource management